URGENSI PEMAHAMAN WAWASAN NUSANTARA BAGI GENERASI MUDA DI ERA GLOBALISASI - Saddam, Saddam; Dwi Sulystyaningsih, Naning; Ketut Sakawibawa, I Dewa; Arifiana Rahmandari, Ismi; Emiliyati (Universitas Islam Zainul Hasan Genggong, 2024)
Abstract Globalization continues to develop and has a significant impact on human life, including the younger generation. Every aspect of life is influenced by social, economic, political and cultural aspects. Understanding the insight of the archipelago is very important in this day and age. where many negative impacts are caused and the lack of understanding of the archipelago's insight by the community, especially the current generation. Based on this, this research aims to provide an understanding to the younger generation of the importance of understanding the archipelago's insight. This research is a literature study that reviews and discusses previous research articles on the importance of understanding archipelago insight for the younger generation. the results obtained are that Archipelago Insight has an important role in realizing the same perception for all Indonesian citizens. Development and socialization of archipelago insight is very important for Indonesian citizens, especially for the younger generation today in the era of globalization which affects all aspects of life that can endanger the unity and integrity of the Indonesian nation.